Evaluación de un catalizador de níquel-cobalto en pellet para el reformado con vapor oxidativo de etanol (OSRE) en un reactor de lecho fijo (2021)
Hydrogen represents a great alternative as an energy vector, due to its physicochemical properties, technical facilities and environmental viability. Although it has several ways to obtain, the OSRE reaction is striking since its raw material (ethanol) has great availability and operating facilities, in addition to integrating the qualities of the SRE and POE reactions. The ESCA research group has been working with transition metal catalysts with hydrotalcite precursor. However, there are no previous studies focused on its extrudate (the most common commercial presentation for these heterogeneous catalysts). The present work seeks to carry out a preliminary evaluation of the extrudate of a Ni-Co catalyst with a hydrotalcite precursor for the OSRE reaction.